Implementasi Model Pembelajaran Kooperatif Pada Madrasah Ibtidiyah - Indana, Nurul; Adi Wijono, Hani (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This article focuses on the implementation of cooperative learning models in Madrasah Ibtidaiyah, particularly in the subject of Aqidah Akhlak. The research is field research because the data produced consists of written or spoken words from objects and observable behaviour. Qualitative research examines the perspectives of participants using multiple interactive strategies, such as direct observation, participatory observation, in-depth interviews, documents, and complementary techniques, such as photographs, recordings, and others. The results of the study show that: The application of the cooperative learning model using the STAD and Jigsaw techniques produces cooperative learning that can increase student learning activity, cooperative learning fosters self-confidence in students, cooperative learning can foster a character of mutual respect, and cooperative learning can improve student learning outcomes. Based on the results of research on the advantages and disadvantages of the Cooperative Learning Model in Aqidah Akhlak subjects, the advantages are that students are more motivated to learn and respond very actively, while the disadvantage of implementing the cooperative learning model is the lack or low level of student motivation to learn.